2010
DOI: 10.5194/hess-14-1745-2010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of prescribed global warming on runoff from headwater catchments of the Irrawaddy River and their implications for the water level regime of Loktak Lake, northeast India

Abstract: Abstract. Climate change is likely to have major implications for wetland ecosystems, which will include altered water level regimes due to modifications in local and catchment hydrology. However, substantial uncertainty exists in the precise impacts of climate change on wetlands due in part to uncertainty in GCM projections. This paper explores the impacts of climate change upon river discharge within three sub-catchments of Loktak Lake, an internationally important wetland in northeast India. This is achieve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…Higher water levels have restricted the areas where this now occurs, leading to a decline in phumdis thickness and, ultimately, loss of structural stability. Singh et al (2010) have demonstrated that climate change may compound the issues associated with elevated lake water level.…”
Section: Loktak Lakementioning
confidence: 99%
See 2 more Smart Citations
“…Higher water levels have restricted the areas where this now occurs, leading to a decline in phumdis thickness and, ultimately, loss of structural stability. Singh et al (2010) have demonstrated that climate change may compound the issues associated with elevated lake water level.…”
Section: Loktak Lakementioning
confidence: 99%
“…This paper initially provides an overview of a water balance model of Loktak Lake and associated catchment hydrological models developed by Singh et al (2010). The water balance model is then used to simulate different options for the operation of the Ithai Barrage that focus on maximizing key ecosystem services, and one that aims to balance the water-level requirements of these different services.…”
Section: Loktak Lakementioning
confidence: 99%
See 1 more Smart Citation
“…One way to resolve this is to construct coherent spatially-variable, multi-sectoral stories from individual climate model scenarios (as in Arnell et al ( this issue a)), but in order to represent uncertainty it is necessary to build many stories. One major lesson learnt in the QUEST-GSI project from Water Arnell et al (2011), Gosling et al (2010Haddeland et al (2011);Arnell and Gosling (2013), Arnell and Gosling (this issue), Gosling and Arnell (this issue) Catchment-scale ), Arnell (2011), Hughes et al (2011, Kingston and Taylor (2010); Kingston et al (2011);Nobrega et al (2011);Singh et al (2010); Thorne (2011), Xu et al (2011 Agriculture and food Fraser et al (2008;; Osborne et al (2012); Simelton et al (2009;; Dawson et al (2014) Coastal zone Nicholls et al (2011);Brown et al (this issue) Terrestrial ecosystems Gottschalk et al (2012) Human health Lloyd et al (2011);Lloyd et al (2015) presentations to different audiences is that different audiences have different requirements so results need to be presented in a wide variety of ways. Some audiences are more concerned with the ranges of potential impacts and are not concerned with whether the extremes can occur at the same time; others are more concerned with synchronous impacts in different places or sectors.…”
Section: Lessons Learntmentioning
confidence: 99%
“…Impacts on hydrological processes by climate change, observed or projected, vary between regions and seasons (Kundzewicz et al 2008). Many studies have been carried out on the sensitivity of water resources to temperature (Somura et al 2009, Kingston and Taylor 2010, Singh et al 2010, Xu et al 2012. Although global temperature apparently increases and the hydrological cycle accelerates, the regional patterns of change in hydrological processes induced by warming are more complex and remain uncertain (Hughes 2000, Milly et al 2005.…”
Section: Introductionmentioning
confidence: 99%